1997
DOI: 10.1002/(sici)1097-4628(19971121)66:8<1495::aid-app10>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polymer blends of poly(lactic acid) and poly(ethylene glycol)

Abstract: Poly(lactic acid) (PLA) and poly(ethylene glycol) (PEG) were melt-blended and extruded into films in the PLA/PEG ratios of 100/0, 90/10, 70/30, 50/50, and 30/ 70. It was concluded from the differential scanning calorimetry and dynamic mechanical analysis results that PLA/PEG blends range from miscible to partially miscible, depending on the concentration. Below 50% PEG content the PEG plasticized the PLA, yielding higher elongations and lower modulus values. Above 50% PEG content the blend morphology was drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
323
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(347 citation statements)
references
References 4 publications
19
323
0
5
Order By: Relevance
“…As N C (and therefore the weight fraction of PEO) increases, T g decreases, consistent with continued dilution of mixed A/C domains by the low-T g component. The presence of only one T g in polymer blends is generally regarded as evidence for miscibility (41,42) and is consistent with the behavior of PLA and PEO homopolymers, which mix over wide ranges of molar masses and blend compositions (43,44). In the analogous LSL′ series, a single T g corresponding to the PLA block is observed that does not change as N A′ increases, because mixed domains inherently remain pure PLA (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 71%
“…As N C (and therefore the weight fraction of PEO) increases, T g decreases, consistent with continued dilution of mixed A/C domains by the low-T g component. The presence of only one T g in polymer blends is generally regarded as evidence for miscibility (41,42) and is consistent with the behavior of PLA and PEO homopolymers, which mix over wide ranges of molar masses and blend compositions (43,44). In the analogous LSL′ series, a single T g corresponding to the PLA block is observed that does not change as N A′ increases, because mixed domains inherently remain pure PLA (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 71%
“…It seems that counter-rotating twin screw extruders could find application for processing of selected biopolymers and biodegradable polymers characterized by low resistance to thermo-mechanical degradation. However, up to now information published in this field are very limited [26,27].…”
Section: Extruders As Chemical Reactors -Basic Conceptsmentioning
confidence: 99%
“…PEG with a value of M n 20 000 very effectively plasticized in a 40 % concentration of poly(L-lactic acid) (Kim et al, 2001). PEG in a concentration above 50 % possesses increased crystallinity, an increased module and decreased ductility (Sheth et al, 1997). Polypropylene glycol also exerts a plasticizing effect on poly(L-lactic acid), its effect on a decrease in crystallinity is lower than in PEG (Kulinski et al, 2006).…”
Section: Oligomeric and Polymeric Plasticizersmentioning
confidence: 99%